2016
DOI: 10.1111/1365-2664.12740
|View full text |Cite
|
Sign up to set email alerts
|

Avian pest control in vineyards is driven by interactions between bird functional diversity and landscape heterogeneity

Abstract: 1. Insectivorous birds are increasingly recognized for the crucial pest control services they provide to agroecosystems. While both the foraging activity and functional diversity of birds are enhanced by multiscale habitat heterogeneity, little is known about how these relationships may influence avian top-down control of insects. Specifically, interactive effects of bird community structure and habitat heterogeneity on pest control across spatial scales have rarely been explored. 2. We sampled bird communitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
86
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 48 publications
(205 reference statements)
8
86
0
Order By: Relevance
“…This latter point relates to suggestions by Barbaro et al. () who showed that narrow‐ranging bird species may be more effective than their wide‐ranging counterparts in contributing to arthropod suppression. This is likely the case in the present study given that herbivorous arthropod abundance related positively to diversity and richness of insectivorous birds.…”
Section: Discussionsupporting
confidence: 74%
“…This latter point relates to suggestions by Barbaro et al. () who showed that narrow‐ranging bird species may be more effective than their wide‐ranging counterparts in contributing to arthropod suppression. This is likely the case in the present study given that herbivorous arthropod abundance related positively to diversity and richness of insectivorous birds.…”
Section: Discussionsupporting
confidence: 74%
“…A few studies have explicitly tested the intermediate landscape‐complexity hypothesis for pest reduction services by avian predators, and the results have been mixed (Barbaro et al. , Birkhofer et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Barbaro et al. () found a negative effect of avian functional evenness on plasticine sentinel prey predation in landscapes with the lowest percentage of seminatural cover, and a strong positive effect of evenness on predation in the landscapes with the greatest amount of seminatural cover. After statistically controlling for the effect of seminatural habitat amount in the landscape, Birkhofer et al.…”
Section: Discussionmentioning
confidence: 99%
“…insects, mites, birds, bats) efficiently acting as predators or parasitoids, which have long been known as natural enemies of viticulture pests. As already noted previously, despite the large amounts of fungicides and insecticides used over decades, the vineyard is far from being a "no parasitoid's land" (Marchesini and Dalla Mont a, 1994;Barbaro et al, 2016; see Thi ery, 2011; for a review). Biological control in vineyards is now promising, but is still a challenging issue, with viticulture still suffering from a lack of basic and applied studies.…”
Section: Beneficial Arthropodsmentioning
confidence: 99%